Development and validation of new diagnostic criteria for atopic dermatitis in children of China. (31st October 2019) - Cheng, R.; Zhang, H.; Zong, W.; Tang, J.; Han, X.; Zhang, L.; Zhang, X.; Gu, H.; Shu, Y.; Peng, G.; Huang, L.; Liu, Q.; et al.
Abstract: Background: In previous epidemiological study, the prevalence of atopic dermatitis (AD) was 12.94% among children aged 1–7 years by clinical diagnosis, whereas that was 4.76% and 3.51% using U.K., and Hanifin and Rajka diagnostic criteria. Objective: We aimed to propose new diagnostic criteria for children and evaluate its efficiency in different populations. Methods: We screened atopic features and analysed their correlation with AD using data from a previous study. A new set of diagnostic criteria for children in China was proposed and validated in 1031 children in outpatient clinics and 538 children in a birth cohort survey. Clinical diagnosis and atopic feature evaluation were performed face to face by dermatologists specialized in AD. Three criteria were compared for diagnostic efficiency using the clinical diagnosis as the reference. Results: The new diagnostic criteria for children were based on (i) pruritus; (ii) 'typical morphology and distribution' or 'atypical morphology and distribution with xerosis'; and (iii) a chronic or chronically relapsing course. Compared to classical diagnostic criteria, the sensitivity of the new diagnostic criteria was significantly higher in the epidemiological survey and the clinical setting, especially obvious among mild and moderate AD. In the birth cohort, the new criteria showed similar sensitivity and specificity. Conclusion: The new criteria for children yielded higher sensitivity for the diagnosis of AD in the epidemiological survey and clinical setting, particularly for mild and moderate AD. Among the birth cohort with a complete medical history, three criteria showed similar sensitivity and specificity. Abstract : Linked Commentary: T. Bieber. J Eur Acad Dermatol Venereol 2020; 34: 438–439. https://doi.org/10.1111/jdv.16223 .